Cost of Organic Fertilizer Production of The Community Fertilizer Producers at Ban San Kang Pla, Sai Moon Sub-District, San Kamphaeng District Chiang Mai Province. - Fonhakeaw, Adisak (RMUTL Journal of Socially Engaged Scholarship, 2023)
The objective of this research was to calculate the cost of organic fertilizer production by the community fertilizer producers of Ban San Kang Pla, Sai Moon Sub-district, San Kamphaeng District, Chiang Mai Province. Data were collected from interviews with groups of organic fertilizer producers and analyzed date by using tables and illustrations for the explanation. The study found that the total production cost of organic fertilizer was 7,420 baht, the production cost of organic fertilizer was 148.40 baht per bag and the gross loss was 49.80 baht per bag, the production cost of organic fertilizer was 7.42 baht per kilogram and the gross profit was 21.58 baht per kilogram. From the calculation of both production costs, the Ban San Kang Pla community fertilizer producers can use it in adjusting strategies and setting product prices.